Muslim Consumers’ Perceptions of Marketing Korea a Muslim-Friendly and Halal Tourism Destination: Future Implications - Tahira, Iffat (Makara Human Behavior Studies in Asia, 2022)
Halal tourism is becoming an emerging niche market to attract Muslim tourists to non-Muslim majority countries. This study aims to assess current conditions associated with the availability of halal-friendly tourism elements and services and future implications for halal tourism in Korea through the lenses of diaspora from Muslim-dominated countries, including Indonesia, Uzbekistan, and Pakistan. A qualitative approach with the descriptive exploratory design was employed and data were collected through in-depth interviews (N = 27) and direct observation. Results in the marketing context indicated that Koreans have basic knowledge of the concept of halal, halal food, halal services, and halal tourism. Muslim residents have a remarkable positive attitude when recommending others to visit Korea as a tourist destination, but the availability of halal tourism is insufficient. Thus, this study contributes to the literature on halal tourism and can serve as an information source for stakeholders and policymakers involved in the halal food market. A few marketing implications are also noted. Muslim consumers are unsatisfied with the facilities of halal tourism. They suggest that tourism organizations, hotel managers, and policymakers improve such facilities according to the sharia-based needs of Muslim tourists.